Estudio de prefactibilidad para la instalación de una planta productora de néctar a base de aguaymanto (Physalis Peruviana) y quinua (Chenopodium Quinoa) endulzado con panela (Saccharum Officinarum) - Charapaqui Paitan, Gina Gladys (2022)
This research work deals with the pre-feasibility study for the installation of a nectar-producing plant based on aguaymanto and quinoa sweetened with panela. For this, in principle, the market has been evaluated and established taking into consideration the most relevant factors, which are technological, economic, financial and social. Second, based on the market study, it is suggested that the final product have a 900 ml presentation. at the price of 8.20 soles to satisfy the public that is in the socioeconomic levels A, B and C of Metropolitan Lima. In this way, the end consumer will be able to purchase and enjoy a quality product that is very beneficial to health. Third, through a Ranking of Factors, the district of Lurín in Metropolitan Lima was selected as the location of the nectar-producing plant. Likewise, this plant will have a production capacity of 340,420 units of nectars in the 900 ml presentation. In fourth place, it is estimated that the investment of this project amounts to S / 539,846.82, which will be financed by third parties with a 40% participation, since 60% will be financed through the own contribution. Therefore, the economic and financial NPV was 824,294.52 and 1,163,526.94, respectively, with an economic and financial IRR of 49.98% and 95.23%, respectively. Likewise, the COK was 10.26%. This demonstrates the viability of the project. It is worth mentioning that the social evaluation of the project will also be analyzed. Finally, the pertinent conclusions and recommendations are detailed.